Onset of canopy closure for black pine, Turkish red pine and Scots pine forests - Kara, Ferhat; Topaçoğlu, Osman (Czech Academy of Agricultural Sciences, 2018)
Canopy closure plays an important role in regeneration and management activities in forestry. Thus, determining the density at which canopy closure occurs is important for the success of silvicultural treatments. Turkish red pine (Pinus brutia Tenore), black pine (Pinus nigra J.F. Arnold) and Scots pine (Pinus sylvestris Linnaeus) forests are usually managed at a density that is near or below the canopy closure. Residual stand density during the management of these species is commonly described by stand basal area - BA (m2.ha-1), however, the BA levels for the canopy closure have not been clearly indicated for these species. The minimum density for the onset of canopy closure (DOCC) was determined for Turkish red pine, black pine and Scots pine forests in this study. DOCC values were compared across the species. For the DOCC, the maximum tree area that a tree can occupy under open-grown conditions was used. The DOCC curves of black pine and Scots pine seem to be similar, but the canopy closure in Turkish red pine forests occurs with fewer trees per hectare for a given mean tree diameter. According to the DOCC curves, regeneration and tending activities will be more practical and effective in these forests.
Keywords: stand density; pinus brutia; pinus nigra; silviculture; Forestry; SD1-669.5; pinus sylvestris; 15. Life on land